Pelatihan Pembuatan Soal Literasi Membaca dan Numerasi Berbasis Asesmen Kompetensi Minimum (AKM) bagi Guru SD Gugus Wahidin Sudirohusodo Kecamatan Jumapolo - Ifa Hanifa Rahman; Anggit Grahito Wicaksono; Muhammad Faruq Hanafi (Jurnal Pengabdian Pada Masyarakat, 2022)
TRAINING ON MAKING LITERACY QUESTIONS FOR READING AND NUMERACY BASED ON MINIMUM COMPETENCY ASSESSMENT FOR ELEMENTARY SCHOOL TEACHERS GUGUS WAHIDIN SUDIROHUSODO, JUMAPOLO DISTRICT. The direction of government policy in measuring students' cognitive learning outcomes is to replace Ujian Nasional (UN) with an Asesmen Kompetensi Minimum (AKM). What is measured in the AKM is the ability to read and numerate literacy as a result of students' cognitive learning. Based on the results of an interview with the Chairperson of the Gugus SD Wahidin Sudirohusodo Kecamatan Jumapolo, some teachers have understood the AKM but have not understood about making reading literacy and numeracy questions based on the Asesmen Kompetensi Minimum (AKM). The results of observations also show that teachers have not been able to make reading and numeracy literacy questions based on the Asesmen Kompetensi Minimum (AKM). The purpose of this service is to provide training on making reading and numeracy literacy questions based on the Asesmen Kompetensi Minimum (AKM). The method of implementing the service includes: (1) the approach method carried out starting from the survey, licensing, and providing motivation for teachers who will take part in the training (2) program implementation methods, including the preliminary stage, the socialization and hearing stage, the implementation stage, and the final evaluation stage. The results of the analysis of teacher responses to the implementation of community service indicate that training materials for making reading literacy and numeracy questions based on AKM are needed by teachers in developing 21st-century learning. Teachers feel the benefits of community service activities because they can become new scientific insights into the development of learning activities in schools.